From Substitution to Solidarity: Towards an Abolitionist Atonement Theology. Issue 4 (19th May 2022) - Bowman, Hannah
ABSTRACT: The emphasis on retribution in American penal culture derives in part from our history of white supremacy and our Christian theological heritage, particularly the doctrine of substitutionary atonement. This essay considers the mutually-reinforcing ways atonement theology has acted in service of racialized narratives of punishment and control, and asks: is it possible to construct a liberatory theology of substitutionary atonement, which can undermine the retributive basis of mass incarceration? It uses the concept of "debt" incurred by harm to read substitutionary atonement as a divine intervention in human violence in two ways: as an interruption of the "transfer" of the debt of harm which defines retribution, and as an act of "doubled divine solidarity" with both victims and perpetrators of violence in a way that respects and does not erase the debt of harm owed to victims. It considers the human response of solidarity, reparations, and abolition such divine intervention provokes.